Colloidal interaction and connectionist modelling of protein osmotic pressure and the effect of physicochemical properties. (31st December 2012) - Rajabzadeh, Amin Reza; Zendehboudi, Sohrab; Lohi, Ali; Elkamel, Ali
Abstract A proper knowledge of the osmotic pressure and thermodynamic behaviour of protein solutions is vital for designing an efficient protein separation process. It is also of great importance to develop a rapid and inexpensive technique to accurately estimate the protein osmotic pressure. A connectionist model to estimate the osmotic pressure of bovine serum albumin (BSA) in terms of pH, ionic strength and BSA concentration is proposed in this paper. Osmotic pressure of BSA is also modelled through the application of a colloidal interaction approach. Molecular interaction forces such as electrostatic, London–van der Waals and hydration along with entropy pressure are considered in the colloidal model to predict the BSA osmotic pressure. The advantages and disadvantages of both modelling approaches are discussed, and a hybrid modelling scheme is proposed for further investigations.